Perceptions and experiences of undergraduate pharmacy students and alumni toward research after exposure to undergraduate research courses - Mukhalalati, Banan; Elshami, Sara; Adlan, Ola; Elshazly, Marwa; Awaisu, Ahmed; Stewart, Derek; Al-Badriyeh, Daoud; Alali, Feras (Frontiers in Medicine, 2022)
Introduction Academic institutions have a duty to equip health professional students with the requisite research skills to ensure the implementation of evidence-based practice. This study aims to determine the perceptions of pharmacy students and alumni toward research after completing Undergraduate Research in Pharmacy Courses (URPCs) at the College of Pharmacy–Qatar University (CPH–QU). Methods A cross-sectional survey was conducted. All CPH-QU alumni (n = 238), and all third- and fourth-year professional students who had completed at least one URPC at the time of conducting the study (n = 42) were approached. The questionnaire contained items relating to research experience and perceptions of significance, confidence in conducting research, actual and anticipated outcomes, and motivation for future research. A Theoretical Domains Framework informed the development of selected items. Results The response rate was 72.1% (202/280); however, the usable rate was 95.5% (193/202). The participants gave positive responses relating to their perceptions of research significance {Median = 5.0 [Interquartile range (IQR) = 1.0], Minimum–Maximum = 1–5}, confidence in conducting research [Median = 4.0 (IQR = 1.0), Minimum–Maximum = 1–5], actual and anticipated outcomes [Median = 4.0 (IQR = 1.0), Minimum–Maximum = 1–5], and motivation for future research plans [Median = 4.0 (IQR = 1.0), Minimum–Maximum = 1–5]. The majority of participants perceived non-confidence in using data analysis software [72 (39.4% non-confidence)] and a high proportion of participants were non-confident in conducting data analysis [45 (24.6% non-confidence)]. More than half reported publishing at least one peer-reviewed article [99 (54.4% agreement)] from their courses and were highly motivated to consider post-graduate degrees in pharmacy [132 (73.3% agreement)]. Conclusions Incorporating URPCs into CPH–QU curriculum has potentially improved students and alumni's perceptions of research. Action is needed to improve confidence in different aspects of research.